LAVH versus NDVH for benign gynaecological diseases: an experience in tertiary care hospital in Uttarakhand - Divya Goswami; Nidhi Kumari; Vineeta Gupta; Priyanka Chaudhary (International Journal of Medical Research and Review, 2016)
Introduction: To study the outcome of Non descent vaginal hysterectomy NDVH, Laparoscopic assisted vaginal hysterectomy LAVH in benign gynaecological conditions and to determine the feasibility of both the routes in terms of safety and simplicity, indications of surgery, intraoperative and postoperative analysis.Methods: The present study is retrospective study of 86 cases of NDVH and LAVH from January 2015 to February 2016 in department of obstetrics and gynecology in Shri Guru Ram Rai Institute of Medical And Health Sciences and Shri Mahant Indiresh Hospital, Dehradun Uttarakhand.Result: Among 86 cases undergoing NDVH and LAVH the most common indication of surgery was Fibroid and DUB. The intraoperative complication rate in NDVH was more compared to LAVH. The operative time and intraoperative blood loss was significantly lower in NDVH group with p <0.001.Conclusion: The present study concludes that NDVH can be safely offered to patients with benign gynecological conditions. LAVH can be offered as a synergistic surgery in cases where difficulty in operative dissection is anticipated.